Genetic diversity and structure of the superabundant whitefly populations, vectors of viruses causing diseases of cassava in three East African countries (Malawi, Tanzania, and Uganda) - (:unkn) unknown (My University, 2019)
High population of the whitefly, Bemisia tabaci Gennadius, a cryptic species complex had been associated with the vectoring and spread of viruses causing two diseases of cassava in East Africa: the cassava mosaic disease (CMD) and cassava brown streak disease (CBSD). Among the B. tabaci species, sub-Saharan Africa 2 (SSA2) was the vector associated with an epidemic of CMD since the 1990s in Uganda. However, this species is now replaced by the SSA1 and led to development of another epidemic by CBSD since the mid 2000s. The spread of both diseases toward South and West Africa is feared with this new supposed invader. In my thesis I have used ecological data and molecular approaches (mitochondrial and nuclear markers) to better understand the factors driving the presence of the superabundant whitefly populations on cassava in East Africa. We have analyzed: i) species abundance, diversity and distribution (geographic and host plants) along a transect survey over three East African countries: Uganda, Tanzania, Malawi, ii) the genetic diversity and structure of current populations of B. tabaci species, and iii) comparing genetic changes between the old and new populations collected in 1997 and 2017, respectively.This study involving large number of samples provided insights of a more complex picture than expected. SSA1 was found to be the source of the some observed outbreaks although other species, notably IO and sub-group 3 of SSA1 (SSA1-SG3) have also shown this capability. The observed outbreaks are therefore not just related to a single species in East Africa. In addition, we showed that the species community and its genetic diversity differ from one country to another, involving different epidemiological situations, without any clear pattern of invasion detected between the countries. Analysis of old samples did not show the involvement of a new species or the emergence of a new population in 20 years, although the dynamics within the whitefly genetic
Keywords: African Research